2012
DOI: 10.4244/eijv8i4a78
|View full text |Cite
|
Sign up to set email alerts
|

The transradial versus the transfemoral approach for primary percutaneous coronary intervention in patients with acute myocardial infarction: a systematic review and meta-analysis

Abstract: This updated meta-analysis demonstrates that transradial PCI reduces the risk of significant periprocedural bleeding and improve clinical outcomes in patients with STEMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
1
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 30 publications
3
44
1
4
Order By: Relevance
“…When stratifying centers by rates of TRA adoption, however, the decline in bleeding outcomes was significantly larger at hospitals with more rapid adoption of TRA than with those with little or no change in TRA utilization. 25 Superior outcomes, including lower rates of bleeding and at times improved in-hospital mortality, have been widely reported for TRA than for TFA in primary PCI for STEMI and include multiple randomized trials, 4,11,13 several recent meta-analyses, 12,[26][27][28] and a large volume of observational data. 1,14,29,30 The majority of randomized data showing clinical benefit from TRA PCI have been from high-volume, experienced providers.…”
Section: Discussionmentioning
confidence: 99%
“…When stratifying centers by rates of TRA adoption, however, the decline in bleeding outcomes was significantly larger at hospitals with more rapid adoption of TRA than with those with little or no change in TRA utilization. 25 Superior outcomes, including lower rates of bleeding and at times improved in-hospital mortality, have been widely reported for TRA than for TFA in primary PCI for STEMI and include multiple randomized trials, 4,11,13 several recent meta-analyses, 12,[26][27][28] and a large volume of observational data. 1,14,29,30 The majority of randomized data showing clinical benefit from TRA PCI have been from high-volume, experienced providers.…”
Section: Discussionmentioning
confidence: 99%
“…Escarcega et al showed that the TRA in coronary procedures is clearly more cost-effective than the TFA, as a consequence of lower requirements for medical and nursing staff in patient management, as well as more rapid return to productivity for working patients with same-day PCI in the TRA group (28). Moreover, some recent studies have demonstrated that coronary interventions with the TRA were associated with shorter hospital stay when compared to the TFA in a wider population of patients (29,30). In the current study, we detected that the length of hospital stay after procedures was 11.6 ± 8.5 h in the total study population, 4.9 ± 0.6 h in those with CAG only, and 28.2 ± 12.8 h in those with AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Although the TRA provides many clinical and economical benefits, maybe the most important advantage is a decreased rate of vascular access-related bleeding complications after PCI [1][2][3][4]. In general, bleeding complications which frequently can be life threatening in the clinical settings of acute coronary syndrome (ACS) have lower rate if TRA is used.…”
Section: Introductionmentioning
confidence: 99%
“…Third, every single operator must have a bailout strategy if radial approach failed to provide quick reperfusion, i.e. fast coronary artery recanalization and restoration of the normal coronary flow [4,5]. …”
Section: Introductionmentioning
confidence: 99%